Incidental Radiological Findings - Weckbach, Sabine (Springer International Publishing : Imprint: Springer, 2017)
This book covers incidental radiological findings (IFs) from different perspectives, provides interesting ethical background information, highlights the differences between IFs in clinical routine and during research studies, explains the management of IFs with reference to practices in different countries. The prevalence of IFs is increasing due to the wider use of modern imaging modalities in routine clinical practice and large population-based cohort studies. The reporting of these findings may lead to further diagnostic investigations and treatment and must therefore be handled with knowledge and care. The management of IFs in clinical routine is regulated by the guidelines of the different academic societies, while management in the setting of research studies depends on a variety of factors. In general, IFs must be disclosed to the imaged subject if they are potentially clinically relevant, but subjects must also be protected from the consequences of false positive findings. This book, written by distinguished experts in their fields, discusses all these issues and will be of interest to radiologists, other clinicians, and radiographers/technicians.
Keywords: Medicine.; Radiology.; Internal medicine.; elektronické knihy; electronic books